INFLUENCE OF SECONDARY METABOLIC PRODUCTS OF ASPERGILLUS FUMIGATUSON THE GERMINATION RATEOF SOME LENTIL TYPES (Sciences & Technologie. C, Biotechnologies, 2009)
Our research purpose to study the effectof the metabolic by-products of the Aspergillus fumigatus fungus on the germination of some types of lentil seeds. Purification has been achieved with organic solvents prior to bar chromatography using an aluminium oxide bar Al2O3,fallowed by thin layer chromatography transported to Silica gel F254 plates. After drying, values of the circulation rate (0.937-0.051)Rf for every resulting spotwere determined. Spots occur with different colours under UV radiation with short wave 254 nm and 365 nm for long waves and likewise in regular light. It allowed determining ten close in their chemical structure. With the study of the impact of different concentrations from secondary metabolic issues secreted by Aspergillus fumigatuson lentil seed germination: sp. I (Syrie), sp. II Large blonde (chili), sp. III Esculata lens (verte). The experiment was designed in sterilized sandy fields inside Petri.The minimal germination percentage rate for the lentil seeds (60.65%) was recorded at concentration 1 mg for Large blonde ( chili) and Escualata lens ( verte), whereas Syrieamounted to 70% at the same concentration. Furthermore, this rate was recorded for Esculata lens( verte)at concentration 100 µg and for LBC type at concentration 1 µg. That means resistance capacity in Syrieexceeds 100, 10 times the ELV and LBC capacity respectively. It should be pointed out that sensitivity in the lentil types started at concentration 0.25 ng and germination percentage was 92.95 and 95% for ELV, LBS, Syrierespectively.